Sensitive detection of voltage transients using differential intensity surface plasmon resonance system - Abayzeed, Sidahmed A.; Smith, Richard J.; Webb, Kevin F.; Somekh, Michael G.; See, Chung W. (Optical Society of America, 2017)
This paper describes theoretical and experimental study of the fundamentals of using surface plasmon resonance (SPR) for label-free detection of voltage. Plasmonic voltage sensing relies on the capacitive properties of metal-electrolyte interface that are governed by electrostatic interactions between charge carriers in both phases. Externally-applied voltage leads to changes in the free electron density in the surface of the metal, shifting the SPR position. The study shows the effects of the applied voltage on the shape of the SPR curve. It also provides a comparison between the theoretical and experimental response to the applied voltage. The response is presented in a universal term that can be used to assess the voltage sensitivity of different SPR instruments. Finally, it demonstrates the capacity of the SPR system in resolving dynamic voltage signals; a detection limit of 10mV with a temporal resolution of 5ms is achievable. These findings pave the way for the use of SPR systems in the detection of electrical activity of biological cells.